0437 Type of Substance Use over Lifetime as a Predictor for Insomnia Complaints. (27th April 2018) - Scott, B V; Dietch, J R; Cloutier, R; Blumenthal, H
Abstract: Introduction: Previous literature on insomnia and substance use has established a bi-directional relationship between insomnia and alcohol dependence(Chakravorty et al., 2016, Johnson & Breslow, 2000, Vitiello, 1997, Conroy & Arnedt, 2014). However, there is little research regarding the relationship between insomnia and use of substances apart from alcohol(Brower & Perron, 2009, Roehrs & Roth, 2001, Conroy & Arnedt, 2014). Furthermore, the association between insomnia symptoms and types of substance use has yet to be explored. The purpose of this study is to examine the relationship between insomnia complaints and types of substance use. Methods: Participants were 1221 healthy college students. Type of insomnia complaint(sleep-onset, maintenance, early awakening) was determined via questionnaire. Lifetime use of substances was determined by questionnaire as well. We conducted three linear regressions for each insomnia complaint and compared them to each type of substance use. Results: We found that lifetime use of non-LSD hallucinogens (β= -.104, p=.028, n=1207) was a significant predictor for sleep onset insomnia complaints, as were lifetime use of sedatives (β= .072, p=.031, n=1206), prescription painkillers (β= .085, p=.015, n=1206) and cigarette smoking (β= .105, p=.005, n=1210). Significant predictors for sleep maintenance insomnia were lifetime use of non-LSD hallucinogens (β= -.107, p=.023, n=1207), anabolic steroids (β= .088, p=.004, n=1208), MDMA (β= -.099, p=.015, n=1206), prescription painkillers (β= .089, p=.014, n=1206) and cigarette smoking (β= .093, p=.013, n=1210). Significant predictors for complaints of waking up too early were lifetime use of sedatives (β= .089, p=.007, n=129), anabolic steroids (β= .099, p=.001, n=129), and MDMA (β= -.082, p=.028, n=129). Lifetime use of alcohol, marijuana, LSD, cocaine, and prescription stimulants were not significant predictors for any insomnia complaints. Conclusion: Contrary to the previous literature regarding alcohol use and insomnia complaints, our study showed no significant relationship between lifetime use of alcohol and insomnia complaints. However, we did find significant relationships between one or more of the examined insomnia complaints and lifetime use of cigarette smoking, non-LSD hallucinogens, sedatives, prescription painkillers, MDMA and anabolic steroids. Future research should explore these relationships further by examining current use of substances as opposed to lifetime use. Support (If Any): None.